The effect of NaOH concentration and seagrass (Syringodium isoetifolium) extract concentration on the characteristics and antioxidant activity of solid soap - Susilo, Bambang; Putri, Salsabilla Kirana; Zalyanti, Nadisa Indra; Azra, Wafa Nida Faida; Rohim, Abd. (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Seagrass (Syringodium isoetifolium) is a marine plant commonly found in Indonesian waters, known to contain bioactive compounds such as antioxidants, anti-inflammatory agents, and antibacterials. This potential makes seagrass a natural ingredient that can be utilized in developing skincare products, one of which is solid soap. This study aims to determine the effect of varying concentrations of NaOH and seagrass extract on the physical characteristics and antioxidant activity of solid soap. The seagrass extraction process was carried out using the ultrasound-assisted extraction (UAE) probe method with 50% ethanol as the solvent. Solid soap was formulated with variations in NaOH concentration (20%, 30%, and 40%) and seagrass extract concentration (0%, 5%, 7.5%, and 10%). Soap quality tests included measurements of moisture content, pH, and foam stability, while antioxidant activity was tested using the DPPH method to determine the IC50 value. The results showed that increasing the NaOH concentration and seagrass extract level tended to increase the moisture content and pH of the soap. The highest foam stability was obtained in soap with 20% NaOH and 10% extract, although the differences were not statistically significant. Antioxidant activity increased with the addition of seagrass extract, with the best result found in soap with 30% NaOH and 10% extract, which had an IC50 value of 1470.90 ppm. The solid soap produced met the solid soap quality standards according to SNI 3532:2021.